Generalized Left Derivations with Identities on Near-Rings (Baghdad Science Journal, 2023)
In this paper, new concepts which are called: left derivations and generalized left derivations in nearrings have been defined. Furthermore, the commutativity of the 3-prime near-ring which involves some algebraic identities on generalized left derivation has been studied.